Analysis of the Golden Ratio on Flowers as an Ecotourism Interpretation in Sukabumi Region - Hidayat, Ristania Fidyani; Ricky Avenzora; Tutut Sunarminto (Media Konservasi, 2025)
The beauty of flowers holds significant appeal for tourists seeking to experience nature. This aesthetic quality can be quantified using the golden ratio, a numerical value associated with beauty. Understanding the golden ratio in flowers offers a fascinating way to enrich ecotourism interpretations for both tourists and flower enthusiasts in Indonesia. This knowledge can transform how visitors appreciate the natural beauty around them. This exploratory research aims to determine the golden ratio's position in 150 flowers found in the Sukabumi Region. A quantitative approach is used to measure and analyze to obtain a comparison that produces a golden ratio value so that the aesthetic value of each flower found in the Sukabumi Region can be known. The results of the golden ratio values were found in nine different variations of the comparison between the morphologies. The golden ratio value on flowers can be used for ecotourism interpretation and adding knowledge regarding the importance of the value of beauty so that it can be managed as a source of tourist attraction in the Sukabumi area.